Women's medicine Sex, family planning and British female doctors in transnational perspective, 1920-70 - Rusterholz, Caroline (Manchester University Press, 2020)
Women's medicine explores the key role played by British female doctors in the production and circulation of contraceptive knowledge and the handling of sexual disorders between the 1920s and 1970s at the transnational level, taking France as a point of comparison. This study follows the path of a set of women doctors as they made their way through the predominantly male-dominated medical landscape in establishing birth control and family planning as legitimate fields of medicine. This journey encompasses their practical engagement with birth control and later family planning clinics in Britain, their participation in the development of the international movement of birth control and family planning and their influence on French doctors. Drawing on a wide range of archived and published medical materials, this study sheds light on the strategies British female doctors used, and the alliances they made, to put forward their medical agenda and position themselves as experts and leaders in birth control and family planning research and practice.